Science on ecosystems and people to support the Kunming-Montreal Global Biodiversity Framework - Schröter, M.; Berbés-Blázquez, M.; Albert, C.; Hill, R.; Krause, T.; Loos, J.; Mannetti, L.M.; Martín López, B.; Neelakantan, A.; Parrotta, J.A.; Quintas-Soriano, C.; Abson, D.J.; et al. (Informa UK Limited, 2023)
In December 2022, members of the Convention on Biological Diversity adopted the new Kunming-Montreal Global Biodiversity Framework (GBF) (https://www.cbd.int/gbf/targets/) to guide international biodiversity conservation efforts until 2030 in order to be able to live ‘in harmony with nature’ by 2050. This framework addresses the implementation gap left after the Aichi Biodiversity Targets, which were the previous global instrument for mainstreaming biodiversity conservation between 2010 and 2020.